HUBUNGAN INDEKS MASSA TUBUH (IMT) TERHADAP SKOR ASTHMA CONTROL TEST (ACT) ANAK PENDERITA ASMA DI WILAYAH KERJA PUSKESMAS KECAMATAN CILANDAK - Dhial Falah Mahasin, (2019)
Asthma is a respiratory illness characterized by obstruction of the airway caused by several risk factors. one those factors is body mass index. Body mass index is a simple way to find out nutritional status in adults and adolescent. This study was conducted by using the asthma control test questionnaire, medical records, as well as height and weight measurements to determine body mass index. The study design used in this research is an observational analytic study with cross sectional design. Data analysis was performed using Kruskall - Wallis method. The results of the study of thirty eight respondents recruited using the non probability sampling method. The study found no significant relationship between the level of asthma control with body mass index (p = 0.187).